Targeting B-cell maturation antigen with GSK2857916 antibody–drug conjugate in relapsed or refractory multiple myeloma (BMA117159): a dose escalation and expansion phase 1 trial. Issue 12 (December 2018) - Trudel, Suzanne; Lendvai, Nikoletta; Popat, Rakesh; Voorhees, Peter M; Reeves, Brandi; Libby, Edward N; Richardson, Paul G; Anderson, Larry D; Sutherland, Heather J; Yong, Kwee; Hoos, Axel; Gorczyca, Michele M; et al.
Summary: Background: B-cell maturation antigen (BCMA) is a cell-surface receptor of the tumour necrosis superfamily required for plasma cell survival. BMCA is universally detected on patient-derived myeloma cells and has emerged as a selective antigen to be targeted by novel treatments in multiple myeloma. We assessed the safety, tolerability, and preliminary clinical activity of GSK2857916, a novel anti-BCMA antibody conjugated to microtubule-disrupting agent monomethyl auristatin F, in patients with relapsed and refractory multiple myeloma. Methods: We did an international, multicentre, open-label, first-in-human phase 1 study with dose escalation (part 1) and dose expansion (part 2) phases, at nine centres in the USA, Canada, and the UK. Adults with histologically or cytologically confirmed multiple myeloma, Eastern Cooperative Oncology Group performance status 0 or 1, and progressive disease after stem cell transplantation, alkylators, proteasome inhibitors, and immunomodulators were recruited for this study. In part 1, patients received GSK2857916 (0·03–4·60 mg/kg) through 1 h intravenous infusions once every 3 weeks. In part 2, patients received the selected recommended phase 2 dose of GSK2857916 (3·40 mg/kg) once every 3 weeks. Primary endpoints were maximum tolerated dose and recommended phase 2 dose. Secondary endpoints for part 2 included preliminary anti-cancer clinical activity. All patients who received one or more doses were included in this prespecified administrative interim analysis (data cutoff date June 26, 2017), which was done for internal purposes. This study is registered withClinicalTrials.gov, numberNCT02064387, and is ongoing, but closed for recruitment. Findings: Between July 29, 2014, and Feb 21, 2017, we treated 73 patients: 38 patients in the dose-escalation part 1 and 35 patients in the dose-expansion part 2. There were no dose-limiting toxicities and no maximum tolerated dose was identified in part 1. On the basis of safety and clinical activity, we selected 3·40 mg/kg as the recommended phase 2 dose. Corneal events were common (20 [53%] of 38 patients in part 1 and 22 [63%] of 35 in part 2); most (18 [47%] in part 1 and 19 [54%] in part 2) were grade 1 or 2 and resulted in two treatment discontinuations in part 1 and no discontinuations in part 2. The most common grade 3 or 4 events were thrombocytopenia (13 [34%] of 38 patients in part 1 and 12 [34%] of 35 in part 2) and anaemia (6 [16%] in part 1 and 5 [14%] in part 2). There were 12 treatment-related serious adverse events and no treatment-related deaths. In part 2, 21 (60·0%; 95% CI 42·1–76·1) of 35 patients achieved an overall response. Interpretation: At the identified recommended phase 2 dose, GSK2857916 was well tolerated and had good clinical activity in heavily pretreated patients, thereby indicating that this might be a promising candidate for the treatment of relapsed or refractory multiple myeloma. Funding: GlaxoSmithKline.